O projecto de uma “metafísica dos costumes” - Lamego, José (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Kant’s idea of a “metaphysics of morals” is indebted to a long tradition, namely the idea of a “Metaphysica moralis” developed by the wolffian school and its historical background, the ontology of the “entia moralia”. The heritage of wolffian ethics is also present in Kant’s theory of ethical self-obligation, through Baumgarten’s theory of obligation. However, this transcendental grounding of obligation only applies to ethical, not to legal obligation: if this is the case, the conclusion should be that the “doctrine of right” is independent of the doctrine of transcendental idealism and that the principle of right cannot be derived from the categorical imperative.